The COVID-19 Hoax as an Islamic Identity Political Movement: Framing Analysis - sulistyanto, Ari; Mujab, Saeful (Journal of World Science, 2022)
The spread of hoaxes is associated with individuals or groups who secretly plan to achieve certain goals. The spread of hoaxes in the midst of the COVID-19 pandemic becomes interesting when hoaxes become a medium for carrying out political movements. The purpose of this study is to uncover hoaxes as an Islamic identity political movement as a means of raising opinions and support. Framing analysis is an approach to analyze hoaxes as a political movement. The results of the study found that China was described as a source of problems from the cause of Covid-19, carrying out Islamic law as an antidote in overcoming Covid-19. This research has implications for mapping the identity politics movement through hoaxes.